Pemanfaatan Jurnal Mingguan untuk Meningkatkan Keterampilan Menulis Kaidah Bahasa di SDN Ngijo 01 Semarang - Salma Ayuning Triana; Husni Maila Wahida; Anisah Rasyidah; Isna Khoirun Nisa; Rifa Nabila Khoirunnisa; Bagas Kurnianto (Badan Penerbit STIEPARI Press, 2025)
This study examines the use of weekly journals as a learning medium to improve the writing skills of language rules among fifth-grade students at SDN Ngijo 01 Semarang. The background of this research is the students’ low ability in applying language rules, particularly in the use of capital letters, punctuation, conjunctions, and proper sentence structure. This research employs a qualitative descriptive method with data collection techniques including interviews, observations, and questionnaires involving both teachers and students. The findings indicate that the consistent implementation of weekly journals can enhance students’ writing skills in terms of structure, accuracy in applying language rules, and confidence in writing. Additionally, the involvement of teachers and parents in providing consistent guidance and feedback plays a crucial role in the success of this program. The results of this study recommend weekly journals as an alternative writing instruction strategy that is effective, enjoyable, and capable of fostering positive literacy habits among elementary school students.